The pharmacokinetic and residue depletion study of eugenol in carp (Cyprinus carpio) - Xu, Yidan; Jiao, Yaqin; Yang, Jian; Tan, Aijuan; Ou, Deyuan; Song, Xuqin; Lv, Shiming (Frontiers in Veterinary Science, 2023)
The pharmacokinetic profile and depletion of eugenol in carp tissue and plasma were performed using a convenient and reliable high performance liquid chromatography (HPLC) method. The eugenol in carp tissues and plasma were extracted with the mixed solution of acetonitrile and methanol. The cleanup was carried out using n-hexane to remove lipid impurities. The average recovery of eugenol at three spiked levels of 1, 10 and 20 μg/g in tissues and 0.1, 1 and 5 μg/mL in plasma were from 70.8% to 107.7%, and the relative standard deviations were less than 7.9%. The limit of detection was 0.05~0.1 μg/g in tissue and 0.008 μg/mL in plasma. The method was successfully applied to the pharmacokinetic study of eugenol in carp plasma and its residue elimination in carp liver, muscle, brain and kidney, following oral administration (medicine bath for carp). The pharmacokinetic parameter of Cmax for eugenol in plasma at the concentrations of 20, 35 and 75 mg/L were 11.45, 16.95 and 36.94 mg/L, respectively. The t1/2α values were 0.2, 0.085, and 0.149 h. After the investigation of the anesthetic effect, 35 mg/L of eugenol was the optimal concentration for anesthesia. The highest accumulation concentration of eugenol in carp is in the liver and the lowest is in the tissue. In addition, the eugenol in tissue was eliminated rapidly and cannot be detected at 48 h. According to the residue elimination, the withdrawal time of eugenol was suggested 3 days.